Prediction of Thermal Strains in Fibre Reinforced Plastic Matrix by Discretisation of the Temperature Exposure History: An Advanced Study - E. K. Ngoy (Novel Perspectives of Engineering Research Vol. 3, 2021)
Prediction of environmental effects on fibre reinforced plastics habitually is made difficult due to the complex variability of the natural service environment. This paper suggests a method to predict thermal strain distribution over the material lifetime by discretisation of the exposure history. Laboratory results show a high correlation between predicted and experimentally measured strain distribution. It is shown that thermal strains due to variable environmental temperature can be predicted by discretization of the exposure history.